2018
DOI: 10.1103/physrevlett.120.205102
|View full text |Cite
|
Sign up to set email alerts
|

Majority of Solar Wind Intervals Support Ion-Driven Instabilities

Abstract: We perform a statistical assessment of solar wind stability at 1 AU against ion sources of free energy using Nyquist's instability criterion. In contrast to typically employed threshold models which consider a single free-energy source, this method includes the effects of proton and He^{2+} temperature anisotropy with respect to the background magnetic field as well as relative drifts between the proton core, proton beam, and He^{2+} components on stability. Of 309 randomly selected spectra from the Wind space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 38 publications
(45 reference statements)
7
68
0
Order By: Relevance
“…Despite these limitations, our numerical results show that fire hose instabilities coexist with plasma turbulence and generate temperature-anisotropy reducing modes that lie in the spectral space outside the region dominated by the turbulent cascade. We expect a similar behavior for other ion kinetic instabilities driven by particle temperature anisotropies and/or differential streaming in the solar wind (as indicated by in situ observations of Klein et al 2018), except possibly for the mirror instability that drives strongly oblique modes; 2-D numerical simulations show that the mirror instability coexists with plasma turbulence ). However, the present simulation results show that these 2-D results are too limited and need to be revisited.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Despite these limitations, our numerical results show that fire hose instabilities coexist with plasma turbulence and generate temperature-anisotropy reducing modes that lie in the spectral space outside the region dominated by the turbulent cascade. We expect a similar behavior for other ion kinetic instabilities driven by particle temperature anisotropies and/or differential streaming in the solar wind (as indicated by in situ observations of Klein et al 2018), except possibly for the mirror instability that drives strongly oblique modes; 2-D numerical simulations show that the mirror instability coexists with plasma turbulence ). However, the present simulation results show that these 2-D results are too limited and need to be revisited.…”
Section: Discussionsupporting
confidence: 62%
“…There are indications that such instabilities are active in the solar wind. Apparent bounds on ion parameters are observed that are relatively in agreement with theoretical kinetic linear predictions (Gary et al 2001;Hellinger et al 2006;Maruca et al 2012;Matteini et al 2013;Klein et al 2018). Furthermore, wave activity driven by the kinetic instabilities associated with the ion temperature anisotropies and/or differential velocity is often observed (Jian et al 2009;Gary et al 2016;Wicks et al 2016).…”
Section: Introductionsupporting
confidence: 73%
“…The various waves analysed here also depend on other plasma parameters such as β j of all species, the number of species, relative drifts among them, and their temperature anisotropies (Marsch et al 1982b,a;Kasper et al 2002;Bale et al 2009;Maruca et al 2012;Verscharen et al 2013;Yoon 2017;Klein et al 2018). It would be useful to repeat our investigation in individual cases when using plasma models with parameters different from the representative values used in this study (Riquelme et al 2015(Riquelme et al , 2016(Riquelme et al , 2018.…”
Section: Discussionmentioning
confidence: 90%
“…While this numerical method has previously been applied to hundreds of intervals from the Wind spacecraft at 1 au (Klein et al 2018), a statistical assessment of linear stability as a function of solar wind and plasma parameters requires analysis of a larger set of data. Additionally, using measurements closer to the Sun than 1 au assists the study of radial variations in inferred stability.…”
Section: Datamentioning
confidence: 99%
“…In this work, we evaluate the stability of 45,147 solar wind observations made by the Helios spacecraft, a subset of observations with a bi-Maxwellian fit for the helium (α) component described in Stansby et al (2019), using a numerical implementation of the Nyquist criterion applied to the hot plasma dispersion relation for an arbitrary number of relatively drifting bi-Maxwellian components (Klein et al 2017b). The Nyquist criterion has been previously applied to hundreds of solar wind measurements made by the Wind spacecraft at 1 au (Klein et al 2018).…”
Section: Introductionmentioning
confidence: 99%